1990
DOI: 10.3109/00365549009037896
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Human Retroviruses in Ogun State of Nigeria

Abstract: We analyzed sera collected during 1987 and 1988 from 385 healthy business employees of both sexes, of Ogun state in Nigeria, for antibodies to the 3 human retroviruses HIV-1, HIV-2 and HTLV-I. No serum was HIV-1 positive, 1 was HIV-2 positive and 2 were HTLV-I positive. A few sera were false-positive in the antibody screening tests which preceded the confirmatory antibody tests. In the confirmatory tests, we found that in the HIV-1 Western blot test 1 serum reacted only with the HIV-1 gag protein p17, and 2 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A recent study from Enugu in South-eastern Nigeria also reported a similar zero (0%) prevalence among prospective blood donors [19]. Some other Nigerian studies have also reported low prevalence of HTLV among different population groups [20,21]. Low prevalence rates have also been reported from some African countries with 0.16% in Dakar, Senegal and 2.3% in Guinea Bissau [22,23].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…A recent study from Enugu in South-eastern Nigeria also reported a similar zero (0%) prevalence among prospective blood donors [19]. Some other Nigerian studies have also reported low prevalence of HTLV among different population groups [20,21]. Low prevalence rates have also been reported from some African countries with 0.16% in Dakar, Senegal and 2.3% in Guinea Bissau [22,23].…”
Section: Discussionmentioning
confidence: 57%
“…More than half of the studies on HTLV carried out in Nigeria utilized only ELISA or other antibody detection methods as means of identifying the virus (Table 3) [40][41][42][43][44][45][46][47][48][49]. This has shown that many of the studies done in Nigeria are without confirmatory tests thereby leaving…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were included from over 500,000 participants in 11 countries. Thirty-six studies (86%) took place in LMICs, with 16 (38%) taking place in Brazil ( 2 , 21–35 ) and the rest being carried out in Peru ( 36–38 ), Guadeloupe ( 39 , 40 ), Mozambique ( 41 ), Nigeria ( 42 , 43 ), Iran ( 44–50 ), Jamaica ( 51 ), Gabon ( 52 ) and Panama ( 53 ) ( Supplementary Table S3 ). Thirty-seven papers assessed level of education in relation to HTLV-1 infection ( 21–39 , 41 , 42 , 44–51 , 54–61 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven papers assessed level of education in relation to HTLV-1 infection ( 21–39 , 41 , 42 , 44–51 , 54–61 ). Eighteen papers assessed income ( 23 , 26–30 , 33 , 35 , 39 , 40 , 43 , 47 , 48 , 50 , 51 , 53 , 56 , 62 ), and six assessed employment status ( 42 , 47 , 50 , 52 , 55 , 59 ). The characteristics of selected studies are summarized in Supplementary Table S3 .…”
Section: Resultsmentioning
confidence: 99%